Development of an Enzyme-Linked Immunosorbent Assay for Serotyping Ureaplasma urealyticum Strains Using Monoclonal Antibodies - Echahidi, Fedoua (American Society for Microbiology, 2001)
Ureaplasma urealyticum comprises 14 serotypes. The existing serotyping methods all use polyclonal antibodies. These methods are time-consuming and labor-intensive, and they cannot always be performed on primary isolates; in addition, the results are difficult to interpret. We developed a new enzyme-linked immunosorbent assay (ELISA) method using serotype-specific monoclonal antibodies (MAbs) to enable the serotyping of U. urealyticum isolates from primary broth cultures. Each of the 14 serotype reference strains was tested against 14 selected MAbs. Homologous reactions were very strong, while heterologous reactions were negligible. Three cross-reactions were observed: MAb 5 cross-reacted with serotype 2, MAb 14 cross-reacted with serotype 3, and MAb 8 cross-reacted with serotype 13. Despite the cross-reactions observed, all the serotype reference strains of U. urealyticum could be identified and differentiated using a combination of MAbs. Reproducibility was analyzed with a fractionated antigenic preparation and with several freshly prepared antigens of the same strain. No significant interrun variation was found with the fractionated antigen, but significant variations in optical density (OD) values were found when freshly prepared antigens were tested. However, the variation in OD values did not influence the overall interpretation of the ELISA: reactions with homologous MAbs were always prominent compared to those of the negative controls. This newly developed ELISA using MAbs seems promising for serotyping of U. urealyticum clinical isolates.